2022
DOI: 10.1049/pel2.12312
|View full text |Cite
|
Sign up to set email alerts
|

An effective utilization scheme for regenerative braking energy based on power regulation with a genetic algorithm

Abstract: To ensure that regenerative braking energy is fully utilized by traction trains in the whole railway power supply systems, an effective utilization scheme of the regenerative braking energy based on power regulation with a genetic algorithm (GA) is proposed in this paper. This scheme consists of railway power conditioners (RPCs), energy transfer converters (ETCs) and a central controller. A RPC connects the two power arms of each TS, and an ETC connects the two power arms of each section post (SP). The RPCs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…In addition, the RPC integrated with an ESS situated in a TSS is also proposed for storing RB energy, and various implementation strategies are suggested [26][27][28][29][30][31]. To improve the RB energy utilisation rate, power converters are used between adjacent power sections in TSSs and section posts [32][33][34]. However, it needs many power converters in both TSSs and section posts, which increases the economic cost of the actual application.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the RPC integrated with an ESS situated in a TSS is also proposed for storing RB energy, and various implementation strategies are suggested [26][27][28][29][30][31]. To improve the RB energy utilisation rate, power converters are used between adjacent power sections in TSSs and section posts [32][33][34]. However, it needs many power converters in both TSSs and section posts, which increases the economic cost of the actual application.…”
Section: Introductionmentioning
confidence: 99%
“…RPC has the advantage of load shifting and flexibility [21,22]. For AC railways, energy storage solutions based on the RPC [23,24] can improve the power quality while utilizing regenerative braking energy. It has therefore received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a reduction in THD of up to 92% and a reduction in negative sequence current of almost 98%. Using the genetic algorithm in [11], the minimum of the total energy losses in the network is sought together with the minimum of the energy extracted from the feeder substations. It is shown that it is possible to use up to 93.3% of the available regenerative braking energy.…”
Section: Introductionmentioning
confidence: 99%